Harnessing the power of traditional Chinese medicine monomers and compound prescriptions to boost cancer immunotherapy - Miao, Keyan; Liu, Weici; Xu, Jingtong; Qian, Zhengtao; Zhang, Qinglin (Frontiers in Immunology, 2023)
Abstract At present, cancer is the largest culprit that endangers human health. The current treatment options for cancer mainly include surgical resection, adjuvant radiotherapy and chemotherapy, but their therapeutic effects and long-term prognosis are unsatisfactory. Immunotherapy is an emerging therapy that has completely transformed the therapeutic landscape of advanced cancers, and has tried to occupy a place in the neoadjuvant therapy of resectable tumors. However, not all patients respond to immunotherapy due to the immunological and molecular features of the tumors. Traditional Chinese Medicine (TCM) provides a new perspective for cancer treatment and is considered to have the potential as promising anti-tumor drugs considering its immunoregulatory properties. This review concludes commonly used TCM monomers and compounds from the perspective of immune regulatory pathways, aiming to clearly introduce the basic mechanisms of TCM in boosting cancer immunotherapy and mechanisms of several common TCM. In addition, we also summarized closed and ongoing trials and presented prospects for future development. Due to the significant role of immunotherapy in the treatment of non-small cell lung cancer (NSCLC), TCM combined with immunotherapy should be emphasized in NSCLC.